Satellite-based mapping of the Universal Thermal Climate Index over the Yangtze River Delta urban agglomeration. (20th December 2020) - Wang, Chenguang; Zhan, Wenfeng; Liu, Zihan; Li, Jiufeng; Li, Long; Fu, Peng; Huang, Fan; Lai, Jiameng; Chen, Jike; Hong, Falu; Jiang, Sida
Abstract: The Universal Thermal Climate Index (UTCI) is an important and frequently used indicator for evaluating thermal comfort. However, there is a lack of city-scale UTCI mapping over urban agglomerations during heat waves, and of studies of the variation of UTCI-based urban heat island intensities across cities. In addition, there is a need to evaluate the relationships among UHI intensities calculated by different types of temperature. In this study of the Yangtze River Delta urban agglomeration (YRDUA), we conducted city-scale UTCI mapping during periods of heat waves, based largely on satellite data. We then compared the UHI intensities in three megacities (Nanjing, Shanghai, and Hangzhou) in terms of the UTCI, and distinguished the differences between UHI intensities based on different types of temperature. Our principal findings are as follows: (1) The UTCI varies considerably with land cover type, with values generally higher in urban areas. Although the spatial pattern of UTCI and air temperature appears similar, over urban surfaces the former indicator is significantly higher than the latter. (2) The areas affected by (very) strong thermal stress (quantified by the UTCI) expanded by 18% and 36.2%, respectively, during daytime and nighttime over the YRUDA from 2002 to 2018. The increase occurred mainly in city peripheries where rapid urbanization has occurred. (3) The UTCI-based UHI intensity (UHII) is lower than those based on land surface temperature (LST) and mean radiant temperature, but greater than those based on surface air and dew-point temperature. The difference among these UHIIs (i.e., UTCI- and other temperature-based measures) over the three selected megacities are relatively small in the day, but they are relatively large at night. Our results are potentially valuable for facilitating city-scale UTCI mapping and for evaluating thermal comfort at the regional scale. Graphical abstract: Image 1 Highlights: City-scale UTCI mapping is achieved mainly using satellite data. Spatiotemporal patterns of UTCI over an urban agglomeration are evaluated. Relationships of UTCI with other surface properties are examined. UTCI-based UHI intensity is compared with those obtained by other temperatures.